Evaluation of an automated breast 3D-ultrasound system by comparing it with hand-held ultrasound (HHUS) and mammography - Golatta, Michael; Baggs, Christina; Schweitzer-Martin, Mirjam; Domschke, Christoph; Schott, Sarah; Harcos, Aba; Scharf, Alexander; Junkermann, Hans; Rauch, Geraldine; Rom, Joachim; Sohn, Christof; Heil, Jörg (Archives of gynecology and obstetrics, 2015)
Purpose: Automated three-dimensional (3D) breast ultrasound (US) systems are meant to overcome the shortcomings of hand-held ultrasound (HHUS). The aim of this study is to analyze and compare clinical performance of an automated 3D-US system by comparing it with HHUS, mammography and the clinical gold standard (defined as the combination of HHUS, mammography and—if indicated—histology). Methods: Nine hundred and eighty three patients (=1,966 breasts) were enrolled in this monocentric, explorative and prospective cohort study. All examinations were analyzed blinded to the patients´ history and to the results of the routine imaging. The agreement of automated 3D-US with HHUS, mammography and the gold standard was assessed with kappa statistics. Sensitivity, specificity and positive and negative predictive value were calculated to assess the test performance. Results: Blinded to the results of the gold standard the agreement between automated 3D-US and HHUS or mammography was fair, given by a Kappa coefficient of 0.31 (95 % CI [0.26;0.36], p\0.0001) and 0.25 (95 % CI [0.2;0.3], p\ 0.0001), respectively. Our results showed a high negative predictive value (NPV) of 98 %, a high specificity of 85 % and a sensitivity of 74 % based on the cases with US-guided biopsy. Including the cases where the lesion was seen in a second-look automated 3D-US the sensitivity improved to 84 % (NPV = 99 %, specificity = 85 %). Conclusion: The results of this study let us suggest, that automated 3D-US might be a helpful new tool in breast imaging, especially in screening.
Published online: 14 October 2014
Gesehen am 13.07.2020